Measuring satisfaction of Islamic business coaching towards small business in the post-pandemic era - Sholahuddin, Muhammad; Abdullah, MohaAsri; Barom, Mohd. Nizam; Tahir, Ibrahim Nuhu; Rahmawati, Rahmawati (SRAC - Societatea Romana Pentru Asigurarea Calitatii, 2024)
This study aims to explore the effectiveness of coaching and business mentoring for business improvement. In the first year, the focus of the research aims to formulate the role of conventional and sharia coaching and mentoring on the performance of small businesses. The second year, analyzing the results of the application of conventional and sharia coaching models produced in the first year on the performance of small businesses. To achieve the goals of this first year, this study used a qualitative method with in-depth interviews as a way of data mining, then analyzed with content analysis. While the second year, analyzed with a quantitative approach. This paper further describes this questionnaire as a four-dimensional use of CFA in testing the validity and reliability of Small Business Success Satisfaction instruments in Indonesia. Quantitative analysis method for a total of 150 respondents of Small Business. The small businessman satisfaction questionnaire is a 7-point likert scale survey consisting of 16 items. The validity and reliability of the Small Business Satisfaction questionnaire was tested with CFA in second order using AMOS version 23. In the hypothesized model used the technique of analysis of affirmative factors order two with three variables latent satisfaction of small business namely financial satisfaction. organist satisfaction and strategic statisfaction. This proves that satisfaction of Islamic business coaching is the driver of sharia small business success which is associated with nine indicators in the dimension of satisfaction, namely productivity, product quality, organizational strength, customer service, complaint reduction, sales growth rate, cost reduction, gross profit, and overall satisfaction/success. In addition, each of these indicators is valid and reliable in four dimensions. The findings of satisfaction of the small business dimension on Islamic business coaching and its construction will benefit business builder practitioners.The implications of the study is the indicators of small business satisfaction using business coaching. In addition, coaching institution who emphasizes service quality rely on small business satisfaction indicators resulting from this study..